An Analysis of the Urdu Translation of the Constitution of the Islamic Republic of Pakistan: A Study of Legal Translation - Inayat, Muqaddas (University of Chitral Journal of Linguistics and Literature, 2023)
The transference of message is important to consider while translating a document from one language system to another. The translator makes changes in this act through the selection of words at semantic, pragmatic, and syntactic levels in order to have equivalence between the two texts. For instance, two culturally different languages like English and Urdu would provide a totally new meaning to the text by experimenting with the words. Hence, the research is conducted to analyze the cultural and semantic lacks faced by the translator besides the brusqueness of expression and emotional feeling that is transferred from the Urdu text into the English text. The following objectives are being gathered from the current study (i) to explore as to what extent the translation of the Constitution of the Islamic Republic of Pakistan has maintained semantic, syntactic and pragmatic equivalence of the source text, (ii) to scrutinize the strategy adopted by most of the translators during the process of translation. According to Chesterman’s (1997) translation method: a qualitative analysis of the contents of ST and TT has been executed by categorizing and scrutinizing the elements of semantic, syntactic and pragmatic shifts. While tracing the important elements of translation shifts in TT, the results of the study prove that Chesterman’s semantic, syntactic and pragmatic translation strategies have aided translators to point out the most favored translation strategies. The findings reflect that translating a legal text is a challenging task as it demands an in-depth understanding of legal phraseology and terminology. Moreover, this thesis helps the researcher in coining new terms in the field of translation.